2008
DOI: 10.1152/ajprenal.00483.2007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of ADP-ribosyl cyclase activation in angiotensin II signaling in murine mesangial cells

Abstract: ribosyl cyclase (ADPR-cyclase) produces a Ca 2ϩ -mobilizing second messenger cyclic ADP-ribose (cADPR) from NAD ϩ . In this study, we investigated the molecular basis of ADPR-cyclase activation and the following cellular events in angiotensin II (ANG II) signaling in mouse mesangial cells (MMCs) signal, but not the transient Ca 2ϩ signal, was blocked by a cADPR antagonistic analog, 8-bromo-cADPR (8-Br-cADPR), and an ADPRcyclase inhibitor, 4,4Ј-dihydroxyazobenzene (DHAB). In support of the results, ANG II stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 44 publications
4
21
0
Order By: Relevance
“…CD38 expression has been reported in some systemic arteries, including aorta and the coronary and renal arteries (8)(9)(10). Endogenous vasoconstrictors, such as norepinephrine, endothelin-1 (ET-1), and angiotensin II (Ang II), have been shown to activate the cyclase and catalase activities of CD38, contributing to the elevation of [Ca 21 ] i and vasoconstriction (11)(12)(13)(14)(15)(16). In general, these vasoconstrictory agonists of G-protein-coupled receptors activate phospholipase C (PLC) to synthesize inositol trisphosphate (IP 3 ) and diacyglycerol from phosphatidylinositol bisphosphate.…”
Section: Clinical Relevancementioning
confidence: 99%
“…CD38 expression has been reported in some systemic arteries, including aorta and the coronary and renal arteries (8)(9)(10). Endogenous vasoconstrictors, such as norepinephrine, endothelin-1 (ET-1), and angiotensin II (Ang II), have been shown to activate the cyclase and catalase activities of CD38, contributing to the elevation of [Ca 21 ] i and vasoconstriction (11)(12)(13)(14)(15)(16). In general, these vasoconstrictory agonists of G-protein-coupled receptors activate phospholipase C (PLC) to synthesize inositol trisphosphate (IP 3 ) and diacyglycerol from phosphatidylinositol bisphosphate.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Several reports indicate that interruption of the renin-angiotensin system (RAS), using the ANG II type 1 receptor (AT1R) blocker or an angiotensin-converting enzyme inhibitor, is clinically effective in slowing the decline of renal function in several nephropathies, including DN (3,10,19). These data support the notion that ANG II can worsen DN.ADP-ribosyl cyclase(s) (ADPR-cyclase) are regulated through G protein-coupled receptor signaling, including the receptor for ANG II (9,11,16,28). The product of ADPR-cyclase, cADPribose (cADPR), modulates Ca 2ϩ fluxes in several types of cells (6, 9, 11).…”
mentioning
confidence: 84%
“…Ang II signaling pathway (adopted from [4]). Stimulation of AT1R by Ang II leads to sequential activation of PI3K, PTK, and PLC1, in turn causing a Ca 2+ release by IP 3 R from ER, resulting in activation of ADPRcyclase.…”
Section: Fig 2 Schematic Model Of Adpr-cyclase Activation Inmentioning
confidence: 99%
“…Mounting evidence has indicated that G protein-coupled receptors, including the angiotensin II (Ang II) receptor, mediate activation of ADPR-cyclase to generate Ca 2+ signaling messengers (3)(4)(5). We have studied Ang II receptor-mediated activation of ADPR-cyclase, resulting in Ca 2+ dysfunction Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation